Preparation of Tetra-Tungstate Red Phosphors and Corresponding White Light-Emitting Diodes - Zeng, Qihua; Liang, Hongbin; Gong, Menglian (Asian Journal of Chemistry, 2013)
Eu3+-activated tungstate phosphors, Ca9Gd2-xEuxW4O24 (x = 0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0), were prepared by the conventional solid-state reaction method. A systematic and exhaustive study for their photoluminescent properties was made. The tungstate phosphors show intensely red emission under 395 and 465 nm light excitation and good Commission International de l'Eclairage (CIE) chromaticity coordinates, therefore can get high colour purity of red emission. Excellent thermal stability for luminescence can also be observed for the tungstate phosphors. Bright red light-emitting diodes (LEDs) and white light-emitting diodes (WLEDs) were fabricated with Ca9Eu2W4O24 phosphor on ca. 395 nm-emitting InGaN chips and about 460 nm blue-emitting InGaN chips, respectively. The good performances of the LEDs demonstrate that the tungstate phosphor is suitable for application of near-UV (NUV) and blue InGaN-based WLEDs.